Epistemic Vigilance, Cautious Optimism and Sophisticated Understanding - Padilla Cruz, Manuel (Research in Language, 2012)
Humans have developed a critical alertness to the believability and reliability of communication: epistemic vigilance (Sperber et al. 2010). It is responsible for trusting interlocutors and believing interpretations. But what is exactly its role in communication? This paper suggests that epistemic vigilance may trigger shifts from a default processing strategy driven by expectations of optimal relevance to more complex processing strategies. These would be enacted when hearers notice speakers’ linguistic mistakes, hearers realise that they have made interpretive mistakes or when hearers discover that speakers seek to mislead them to erroneous or unintended interpretations.